A Resilience Assessment Framework for Hybrid Monolithic-Microservices Systems: A Comparative Case Study of Odoo ERP Integration - Alex Kurniawan (Sean Institute, 2026)
The migration of traditional monolithic Enterprise Resource Planning (ERP) systems to modern architectures often results in complex hybrid systems where a core monolith coexists with new microservices. These hybrid models present significant challenges in ensuring end-to-end reliability and observability. This paper proposes and validates a systematic framework for identifying, analyzing, and resolving performance bottlenecks in such environments, targeting the ISO/IEC 25010 reliability sub-characteristics: Maturity, Availability, Fault Tolerance, and Recoverability. Employing a quantitative pre-test/post-test methodology, a hybrid Odoo-NestJS system was instrumented with a comprehensive observability stack and subjected to targeted stress tests using k6. Baseline tests revealed critical vulnerabilities, including a 7.80% failure rate during resource-intensive requests and severe cascading failures. By implementing targeted architectural interventions, namely asynchronous worker pools, request timeouts, and retry patterns, the optimized system achieved a 100% reduction in processing failures, doubled its throughput, and reduced user-facing downtime errors by 88%. The findings validate that specific operational patterns provide substantial, quantifiable improvements to system stability in a hybrid monolithic-microservice context.